The NA62 level 0 calorimetric trigger fast readout implementation, commissioning and data taking performances. (1st February 2023) - Ammendola, R.; Battista, D.; Paoluzzi, G.; Salamon, A.; Aliberti, R.; Barbanera, M.; Bonaiuto, V.; Ceccucci, A.; Checcucci, B.; De Simone, N.; Fantechi, R.; Federici, L.; et al.
Abstract: The NA62 experiment at the CERN SPS aims to measure the branching ratio of the very rare kaon decay K + → π + ν ν ¯ . The Calorimetric Level 0 Trigger identifies clusters in the electromagnetic and hadronic calorimeters. Along with the trigger data sent to the L0 Trigger Processor, readout data is collected to be sent to the L1 software trigger. In this work we present the novel implementation of the readout data collection and forwarding system in the multiple layers of the calorimetric trigger structure. We will also present the commissioning of the system and the performance evaluation on current data taking.